2019
DOI: 10.1111/trf.15397
|View full text |Cite
|
Sign up to set email alerts
|

The effects of monoclonal anti‐CD47 on RBCs, compatibility testing, and transfusion requirements in refractory acute myeloid leukemia

Abstract: BACKGROUND: CD47 is a novel therapeutic target in Abbreviations: AML = acute myeloid leukemia; B-NHL = B-cell non-Hodgkin lymphoma; DAT = direct antiglobulin test; DTT = dithiothreitol; Hb = hemoglobin; IAT = indirect antiglobulin test. From the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 19 publications
0
83
0
Order By: Relevance
“…As seen with CD38 blocking agents, including daratumumab, [7][8][9] CD47 blocking agents generate panreactivity in IAT, interfering with pretransfusion compatibility testing. 10,11,16,17 While plasma from patients treated with daratumumab typically shows weak reactivity in IAT, 18 plasma from patients treated with Hu5F9-G4 or ALX148 exhibits strong reactivity in IAT. 10,16,17 Similarly, in our study, strong reactivity (3+) in gel IAT was observed in the plasma from all four patients treated with ALX148.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen with CD38 blocking agents, including daratumumab, [7][8][9] CD47 blocking agents generate panreactivity in IAT, interfering with pretransfusion compatibility testing. 10,11,16,17 While plasma from patients treated with daratumumab typically shows weak reactivity in IAT, 18 plasma from patients treated with Hu5F9-G4 or ALX148 exhibits strong reactivity in IAT. 10,16,17 Similarly, in our study, strong reactivity (3+) in gel IAT was observed in the plasma from all four patients treated with ALX148.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotyping of patient RBCs for extended antigen-matched blood transfusion can be accomplished using antigen typing reagents at the IS or RT phases, even after ALX148 administration. The increasingly widespread T A B L E 3 Comparison of interference in pretransfusion compatibility testing and mitigation strategies between Hu5F9-G4 10,11 and ALX148 (our study) [15][16][17] Hu5F9-G4 ALX148 use of MoAbs and fusion proteins with unintended binding to RBCs poses a growing challenge to blood banks. International efforts should be undertaken to investigate the potential of each drug to interfere with pretransfusion compatibility testing and establish a guideline to solve the problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enthusiasm surrounding the clinical utility of SIRPa/CD47 inhibition is somewhat tempered by expression of CD47 on erythrocytes and platelets, and the associated risk of hemolysis and thrombocytopenia (21,42,45). The Fc domain of hSIRPa-Fc-CD40L does not bind effector Fc receptors ( Supplementary Table S2), and in vitro studies did not reveal evidence of hemolysis in human or cynomolgus macaque erythrocytes ( Supplementary Fig.…”
Section: Safety and Activity Of Sirpa-fc-cd40l In Nonhuman Primatesmentioning
confidence: 99%
“…Hu5F9-G4 is a novel anti-CD47 monoclonal IgG4 antibody under evaluation in six studies in the United States and United Kingdom. 3,4 In the UK, the CAMELLIA study is a Phase 1 dose escalation trial of Hu5F9-G4 in haematologic malignancies including relapsed/refractory acute myeloid leukaemia/highrisk myelodysplasia (NCT02678338).…”
mentioning
confidence: 99%